Genetic factors underlying the risk of thalidomide-related neuropathy in patients with multiple myeloma - Johnson, David C.; Corthals, Sophie L.; Walker, Brian A.; Ross, Fiona M.; Gregory, Walter M.; Dickens, Nicholas J.; Lokhorst, Henk M.; Goldschmidt, Hartmut; Davies, Faith E.; Durie, Brian G. M.; Ness, Brian Van; Child, J. Anthony; et al. (Journal of clinical oncology, 2011)
Purpose To indentify genetic variation that can modulate and predict the risk of developing thalidomide-related peripheral neuropathy (TrPN). Patients and Methods We analyzed DNA from 1,495 patients with multiple myeloma. Using a custom-built single nucleotide polymorphism (SNP) array, we tested the association of TrPN with 3,404 SNPs. The SNPs were selected in predicted functional regions within 964 genes spanning 67 molecular pathways thought to be involved in the pathogenesis, treatment response, and adverse effects associated with myeloma and its therapy. Patient cases and controls were derived from two large clinical trials that compared thalidomide with conventional-based treatment in myeloma patients (Medical Research Council Myeloma-IX and HOVON-50/GMMG-HD3). Results We report TrPN associations with SNPs—ABCA1 (rs363717), ICAM1 (rs1799969), PPARD (rs2076169), SERPINB2 (rs6103), and SLC12A6 (rs7164902)—where we show cross validation of the associations in both trials. To investigate whether TrPN SNP associations were related to exposure to thalidomide only or general drug-related peripheral neuropathy, we performed a second analysis on patients treated with vincristine. We report SNPs associated with vincristine neuropathy, with a seemingly distinct underlying genetic mechanism. Conclusion Our results are consistent with the hypothesis that an individual's risk of developing a peripheral neuropathy after thalidomide treatment can be mediated by polymorphisms in genes governing repair mechanisms and inflammation in the peripheral nervous system. These findings will contribute to the development of future neuroprotective strategies with thalidomide therapy and the better use of this important compound.
Gesehen am 05.07.2022